Qualitative study of social determinants of child marriage in Kurdish regions of Iran: Evidence for health promotion interventions - Javad Yoosefi Lebni; Mahnaz Solhi; Farbod Ebadi Fard Azar; Farideh Khalajabadi Farahani (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: One of the most thought-provoking problems in the world is child marriage that is affected by various factors. Therefore, the purpose of this study is to identify the social determinants of child marriage in Kurdish regions of Iran. MATERIALS AND METHODS: This qualitative study was conducted using conventional content analysis approach. The participants of the study were 30 Iranian-Kurdish women married under the age of 18 who were selected through purposeful and snowballing sampling. Data collection was conducted through semi-structured interviews and face-to-face interviews and continued until the saturation of concepts was achieved. Graneheim and Lundman method was used to analyze the data, and Guba and Lincoln criteria were used to strengthen the research. RESULTS: In general, findings include 5 categories and 17 subcategories: 1 - economic factors (financial problems and economic benefits); 2 - sociocultural factors (social customs, cultural beliefs, community encouragement, social learning, gaining prestige, and social support); 3 - individual factors (physical characteristics, personality traits, lack of awareness of the damaging consequences of early marriage, and fear of the future); 4 - family factors (dysfunctional family, weak awareness of parents, and harm prevention); and 5 - structural factors (high demand, limited access to educational services, and the lack of supportive social and legal structures). CONCLUSION: By raising the level of awareness and attitude of girls and their families about the consequences of early marriage, creating the culture of correcting cultural beliefs and social misconceptions, passing appropriate laws, and the use of local and national media to prevent child marriage, this social harm can be reduced.